Cerebellar hypoplasia and quadrupedal locomotion in humans as a recessive trait mapping to chromosome 17p. Issue 5 (21st December 2005) - Türkmen, S; Demirhan, O; Hoffmann, K; Diers, A; Zimmer, C; Sperling, K; Mundlos, S
Abstract : Background: Congenital hereditary non-progressive hypoplasia of the cerebellum is a rare condition, frequently associated with other neuropathology such as lissencephaly. Clinically, the condition is associated with variable degrees of mental retardation, microcephaly, seizures, and movement disorders due to ataxia. In severe cases, patients are unable to ambulate independently, but nevertheless do use bipedal locomotion. Methods and Results: Here we present a family with seven affected members, five of whom never learned to walk on two legs but have fully adapted to quadrupedal palmigrade locomotion. These subjects show signs of cerebellar ataxia and are mentally retarded. MRI analysis demonstrated hypoplasia of the cerebellum and the cerebellar vermis as well as a small nucleus dentatus and a thin corpus callosum but no other malformations. We show, by a genome-wide linkage scan, that quadrupedal locomotion is a recessive trait linked to chromosome 17p. Conclusions: Our findings have implications for understanding the neural mechanism mediating bipedalism, and, perhaps, the evolution of this unique hominid trait.